Magnetohydrodynamic simulations of runaway electron beam termination in JET. (29th January 2021) - Bandaru, V; Hoelzl, M; Reux, C; Ficker, O; Silburn, S; Lehnen, M; Eidietis, N; Team, JOREK
Abstract: A runaway electron (RE) fluid model is used to perform non-linear magnetohydrodynamic simulations of a relativistic electron beam termination event in JET. The case considered is that of a post-disruption low density cold plasma in the runaway plateau phase, wherein high-Z impurities have been largely flushed out via deuterium second injection (Shot:95135). Details of the experiment are found in separate publications. Our studies reveal that a combination of low plasma density and a hollow current profile which is confirmed by experimental studies causes fast growth of a double-tearing mode, which in turn leads to stochastization of the magnetic field and a prompt loss of REs. The phenomenology of events leading to the crash and the timescales of the dynamics are in excellent agreement with the experiment. Simulations also indicate significant toroidal variation in RE deposition but without localized hotspots. The strong stochastization setting in first from the edge leads to a poloidally broad deposition footprint that partly explains the benign nature of the termination event. This work further supports the potential possibility to engineer a benign RE beam termination scenario via deuterium second injection in ITER, as proposed by Reux et al 'Runaway electron beam suppression using impurity flushing and large magnetohydrodynamic instabilities' (submitted to Physical Review Letters ).